A SIMPLE METHODOLOGY TO SEGMENT X-RAY TOMOGRAPHIC IMAGES OF A MULTIPHASIC BUILDING STONE - Trong, Emmanuel Le; Rozenbaum, Olivier; Rouet, Jean-Louis; Bruand, Ary (Image Analysis and Stereology, 2011)
Assessment of the weathering of a particular limestone, the tuffeau, used in historical monuments requires an accurate description of its microstructure. An efficient tools to obtain such a description is X-ray microtomography. However the segmentation of the images of this multiphasic material is not trivial. As the identification of pertinent markers of the structural components to extract is difficult, a two steps filtering approach is chosen. Alternate sequential filters are shown to efficiently remove the noise but, as they destroy the structural components smaller than the structuring element used, they cannot be carried out far enough. Hence as a second step in the filtering process, a mosaic operator, relying on a pragmatic yet efficient marker determination, is implemented to simplify further the images.